Brand Trust Amplifies Word of Mouth, Boosts Repurchase Intention in Indonesia: Kepercayaan Merek Memperkuat Promosi dari Mulut ke Mulut, Meningkatkan Niat Beli Ulang di Indonesia - Rachmawati , Errina; Detak Prapanca (Indonesian Journal of Law and Economics Review, 2024)
This study examines how celebrity endorsers and word of mouth influence repurchase intention for Scarlett Whitening products in East Java, with brand trust as a moderating variable. Using a questionnaire and purposive sampling, data from 96 respondents were analyzed with path analysis via PLS software. The results show that both celebrity endorsers and word of mouth positively impact repurchase intention, with brand trust also playing a significant role. However, brand trust moderates the effect of word of mouth but not celebrity endorsers on repurchase intention. These findings suggest focusing on enhancing word of mouth and maintaining brand trust to boost repurchase intentions. Highlights: 1. Positive Impact: Endorsers and word of mouth boost repurchase intention. 2. Moderation: Brand trust enhances word of mouth, not endorsers’ impact. 3. Strategy: Focus on word of mouth and brand trust. Keywords: Celebrity Endorser, Word of Mouth, Brand Trust, Repurchase Intention, Scarlett Whitening